A mini-review of traditional Chinese medicines on liver diseases - Siu Kan Law; Dawn Ching Tung Au; Albert Wing Nang Leung; Chuanshan Xu (Pharmacological Research - Modern Chinese Medicine, 2023)
Introduction: Currently, around 2 million deaths per year are attributed to liver disorders worldwide. There are many traditional Chinese medicines (TCM) and natural products used for preventing and combating liver disorders in China, such as “Celastrol”, “Astragalus”, and “Curcumin”. This mini-review aims to discuss the (i) TCM theory, (ii) pharmacology mechanisms, and (iii) toxicology of the commonly used TCMs, such as “Celastrol”, “Astragalus”, “Curcumin” in the treatment of liver diseases, and further (iv) describe the help of modern “Nanotechnology” with these TCMs in future development for curing liver diseases. Methods: Nine electronic databases were searched between 2012 and 2022, including WanFang Data, PubMed, Science Direct, Scopus, Web of Science, Springer Link, SciFinder, and China National Knowledge Infrastructure (CNKI), without regard to language constraints. The searched keywords include “Celastrol + liver diseases”, “Astragalus + liver disease” ''Curcumin + liver diseases'', etc. All eligible studies are analyzed and summarized in this review. Results: Celastrol, Astragalus, and Curcumin were reported to be effective Chinese herbals for the prevention and treatment of liver diseases through cyclic adenylate monophosphate (cAMP)–protein kinase A (PKA)–nuclear factor kappa-B (NF-κB), miR-712-PPAR-γ-PI3K/AKT-GLUT4, and phosphatidylinositol 3-kinase (PI3K)/protein kinase B (AKT)/mammalian target of the rapamycin (mTOR) signaling pathways. Nanoformulations could improve physiochemical features and enhance the efficacy of Chinese herbs. Conclusion: Celastrol, Astragalus, and Curcumin as commonly used TCMs for the treatment of liver diseases possess a wide extent of pharmacological functions, such as anti-inflammatory, anti-oxidant, and anti-cancer properties. Nanoformulations of Chinese herbs show great promise in the development of traditional Chinese medicines for treating liver diseases.